Thematic Analysis of Parental Perception in Choosing Bimba as Early Childhood Education Compared to Kindergarten - Kezia Revina Kusumaningrum; Sulfani Nur Mawaddah; Zetamilla Qayyima; Indri Hapsari (Universitas Ahmad Dahlan, 2026)
A growing shift in parental preference from kindergarten to Bimba has emerged in Early Childhood Education (ECE) in Indonesia. This research aimed to explore parental perceptions in choosing Bimba as the sole ECE for their children. A qualitative case study was conducted with six participants. Data were collected through semi-structured interviews, in which participants also presented audio-visual materials about children’s learning activities. Data were then analyzed using thematic analysis. Four main themes were identified: parental concern, image of kindergarten in parents’ eyes, strengths of bimba, and financial consideration. These findings suggest that parental decisions are shaped by both immediate practical needs and systemic educational expectations. The study highlights the importance of strengthening public understanding of the goals and role of ECE in Indonesia.